(untitled) (Veterinary Science, 2017)
The mathematical model allow to predict the microorganisms’ growing speed according to environmental such a temperature and pH. The models con be classified in three levels: 1(Gompertz’ model), 2 ( Arrhenius equation) and 3 (expert computer systems). Food duration and safety as well microbial stability coming from new foodstuffs can we predicted and determined respectively. These equations also help to evaluate possible health risks. Ways of applying these models to Klebsiella sp. (in a model system in meat product) are shown in this work